Faith, Love, and Literacy Practices: The Teaching and Learning of Qur’an and Arabic Language of Multicultural Muslims in a Single Sex Class - Irfan Rifai; Fadillah Sandy (Universitas Teuku Umar, 2019)
This article reports the literacy teaching and learning of a boys-only weekend class in a mosque of a midwestern city, United States. As part of the Muslim’s community who regularly attended the weekend class that studied Qur’an and Arabic, I interviewed the participants (teacher, principal, students, and parents), observed their class interactions, took notes during and after the interactions, and gathered some artifacts that portrayed the interactions and the teaching and learning processes. Coming from various cultural background, the students and teacher demonstrated shared motivation, yet divergent interpretations on the objective and the teaching learning interactions. Taking the perspectives of ethnography of communication (Hymes, 1964; Cameron, 2001), I found that the literacy practices in this community was motivated by the love and piety of God, strong ties to their cultural background, and the perpetuation of both faith and cultural identity.